Understanding knowledge creation processes among rural communities in post-conflict settings in Colombia - Rosalba Frias-Navarro; Luz Alexandra Montoya-Restrepo (Knowledge Management & E-Learning: An International Journal, 2020)
The purpose of this research was to identify how the knowledge creation process (KCP) takes place among Suyusama, an organization that carries out specific extension functions and advisory services, and the rural communities in Nariño, Colombia. Specifically, the study determined how new knowledge was created, disseminated, and materialized into products, services or systems. Colombia, as a country emerging from conflict, faces considerable challenges to improve rural livelihoods in its agricultural sector. To gain productivity and food security within a sustainable management of natural resources requires a conceptual framework for planning and implementing programs to strengthen agricultural extension and advisory systems. Grounded Theory Methodology was employed in order to create theory from the systematic analysis of data, obtained from field observations and in-depth interviews with members of the local community organizations. The result was a theoretical explanation of the KCP that occurs from the autonomous work of the community with the accompaniment of a mentor organization in a multicultural and diverse meeting scenario, where the dialogue of knowledge and cooperation is promoted by integrating traditional and contemporary knowledge. This work is also an academic contribution to exemplify the distinction between tacit and explicit knowledge and the interorganizational ontological dimension in which a knowledge -creation spiral takes place in a rural context.